HOW IS THE SIMULTANEOUS APPROACH BETWEEN IMPORT AND AGGREGATE CONSUMPTION IN INDONESIA? - Dewi Mahrani Rangkuty; Anwar Sanusi; Adjie Hermawansyah (Journal of Research in Business, Economics, and Education, 2020)
The research aims to analyze imports and consumption of Indonesia. With the simultaneous equation method of the 1987-2017 time-series data from the World Bank. The results showed that foreign exchange reserves, inflation, and significant consumption influenced the change in Indonesia's import developments. Foreign exchange reserves and consumption is inelastic against imports whereas inflation is elastic against imports. GDP, debt interest and imports significantly affect the change in Indonesia's consumption development. GDP is elastic against consumption while debt and import interest are inelastic towards consumption. Inelastic consumption of the import and import of inelastic to consumption, meaning that the change in price and the value of both economic variables in Indonesia during the period of research is to be responded insensitively by domestic communities. Suggestion to the Government that the Ministry of Trade keeps the regulation the import quota reduces dependence on products abroad and encourages the productivity of the domestic real market industries. Thus consumption of local products that then increases domestic economic growth.